Case Report and Literature Review: Primary Pulmonary NUT-Midline Carcinoma - Zhang, Yunxiang; Han, Kai; Dong, Xiaotong; Hou, Qian; Li, Tianbao; Li, Li; Zhou, Gengyin; Liu, Xia; Zhao, Guifeng; Li, Wei (Frontiers in Oncology, 2021)
Nuclear protein of the testis (NUT) carcinoma is a very rare and aggressive carcinoma characterized by chromosomal rearrangement. NUT midline carcinoma (NMC) can occur in anywhere of the body, but most of the tumors are found in the midline anatomic structure or mediastinum. Pulmonary originated NMC is extremely rare and often difficult to be distinguished from other poorly differentiated tumors, therefore, making the diagnosis awfully challenged in clinical practice. There are less than 100 cases of NUT carcinoma reported so far. In this study, the diagnosis and molecular mechanisms of reported NUT carcinoma cases were reviewed. Furthermore, a case of primary pulmonary NUT-midline carcinoma and its pathological features was reported. The process of pathological identification and genomic analysis for establishing the diagnosis was discussed. We found that NUT carcinoma could be identified by combining PET/CT, H&E staining, immunohistochemistry (IHC) and molecular tests. The development of NUT carcinoma might be associated with mutation of MYC, p63 and MED24 genes, and the Wnt, MAPK and PI3K signaling pathways. Our study provided detail molecular mechanistic review on NMC and established a procedure to identify pulmonary NMC.